Educational Text Based on Literary Text: the Ways of Second Linguistic Personality Formation (Proceedings of Southern Federal University. Philology, 2018)
Yulia E. Kachan, Margarita V. Ereshchenko (Rostov-on-Don, Russian Federation)The article deals with the formation of foreigners’ second linguistic personality by training reading, understanding and interpreting literary texts. A doubled cognitive consciousness is formed by immersion in a new language environment. The levels of linguistic personality (lexicon, thesaurus, pragmatics) are gradually being connected. The development of foreigner’s ability to communicate with representatives of a different culture is still relevant. Acquaintance with culture, history, traditions, way of life, Russian national character is possible only through authentic literary texts. The method of pedagogical experiment has been used as a method of research to find and choose the most effective tasks.Key words: Russian literary text, secondary language person, interpretation, authentic text, educational text.DOI 10.23683/1995-0640-2018-3-222-230